PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS UNTUK REKOMENDASI ASISTEN DOSEN TERBAIK (STUDI KASUS: UNIVERSITAS AMIKOM YOGYAKARTA) - Bondan Wahyu Pamekas; Kusrini Kusrini; Emha Taufiq Luthfii (Universitas Janabadra, 2020)
Assistant forum is one of the organizations under the direct guidance of University AMIKOM Yogyakarta, which serves as a forum for practicum assistants. Practical assistant or lab assistant in charge of assisting lecturers in lecture activities. The assistants are active college students and have passed the selection. At the end of each semester an evaluation is held to make it better in the future as well as giving awards to assistants. The awarding of course is a selection process. Therefore a system is needed that can help provide recommendations in accordance with previously determined criteria. In a decision support system there are various methods that can be used, one of them is the Analytical Hierarchy Process method. The process is done by entering assistant data into this method. Then do the calculation by determining the weight of each criterion. The results of this study to test the method that will be applied to this model so that it has accuracy that can be used as a reference in helping to determine the best assistant with ranking.Keywords: Decision Support System, Analytical Hierarchy Process, Recommendation